A Comparison Between The Administration of Povidone Iodine 10% and Aloe Vera Gel on The Healing of Wistar Rat Burns (Rattus Norvegicus) - Jesselyn Felicia; Dewi Fibrini; Anita Rosari Dalimunthe (Green Publisher Indonesia, 2024)
Aloe vera has long been known for its diverse properties, including wound healing. Compounds such as saponins, tannins, and polyphenols contained in aloe vera provide anti-inflammatory, antibacterial, and accelerate tissue regeneration. This study aims to compare the effectiveness between Povidone Iodine 10% and Aloe Vera Gel on burn wound healing in Wistar Rats (Rattus norvegicus). The study used an experimental design with post-test only control group design. A total of 33 rats were divided into three groups: control group without treatment, Povidone Iodine 10% group, and Aloe Vera Gel group. Observations were made on days 0, 7, and 14 with parameters of wound diameter, percentage of wound reduction, and histopathological analysis to assess the amount of blood vessel formation, fibroblasts, macrophages, and epidermal thickness. The results showed that the administration of Aloe Vera Gel is effective in healing burn wounds, especially in the inflammatory and proliferation phases.